Creating value added in the coffee industry in kerinci: government policy, capital structure, social capital, entrepreneurial ecosystem and global market competition - Syofya, Heppi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study examines value-added development in the coffee company in Kerinci, with a focus on the relationships between capital structure, social capital, the entrepreneurial ecosystem, and the competitive worldwide market. This work employed a quantitative approach with a survey of 185 samples serving as the main data collection instrument, and SEM-PLS 4 was used for data analysis. The results validated the hypothesis that policy measures, optimal capital structure, and robust social capital underpin the expansion of the entrepreneurial ecosystem. Furthermore, it has been demonstrated that a robust entrepreneurial ecosystem plays a critical role in enabling coffee entrepreneurs to compete globally and create value. By illuminating the complex dynamics of the coffee industry in Kerinci and providing helpful advice for industry participants, including policymakers, this study advances the body of knowledge.